2018
DOI: 10.1021/acs.jpclett.8b01719
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Characterization of an n → π* Interaction in a Pyridine–Formaldehyde Adduct

Abstract: The rotational spectrum of the pyridine-formaldehyde adduct generated in a supersonic expansion has been analyzed using Fourier transform microwave spectroscopy. The spectrum shows a quadrupole coupling hyperfine structure due to the presence of N. The spectra of the parent species,C and N isotopologues, have been observed to investigate its structure. The complex shows C symmetry with the plane of pyridine bisecting the ∠HCH angle of formaldehyde and the N atom located along the Bürgi-Dunitz trajectory of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 41 publications
5
44
1
Order By: Relevance
“…Further, the lone pairs of oxygen and the antibonding π orbital of the CO bond of the carbonyl group can be involved in orbital interactions with appropriate acceptor and donor atom orbitals, respectively. These properties make the carbonyl group unique and it can participate in many distinct noncovalent interactions such as hydrogen bonding1 (CO···H), carbonyl–chalcogen interactions2 (CO···X; X = S, Se, and Te) and nucleophile–carbonyl interactions3 (Nu···CO) in chemical and biological systems. While hydrogen bonding and carbonyl–chalcogen interactions are well studied, relatively less is known about Nu···CO interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the lone pairs of oxygen and the antibonding π orbital of the CO bond of the carbonyl group can be involved in orbital interactions with appropriate acceptor and donor atom orbitals, respectively. These properties make the carbonyl group unique and it can participate in many distinct noncovalent interactions such as hydrogen bonding1 (CO···H), carbonyl–chalcogen interactions2 (CO···X; X = S, Se, and Te) and nucleophile–carbonyl interactions3 (Nu···CO) in chemical and biological systems. While hydrogen bonding and carbonyl–chalcogen interactions are well studied, relatively less is known about Nu···CO interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its interest, only a few rotational spectroscopy studies have shown these interactions to occur in molecular complexes. [20][21][22] Pyridine (PY) or its derivatives can be used as nucleophilic catalysts in acylation reactions. 23 The structures of pre-reactive intermediates of PY with carbonyl compounds are expected to show the signatures of the n* interactions as recently observed for the PY-formaldehyde (FA) adduct.…”
mentioning
confidence: 99%
“…The axis of the N lone pair electrons lies in the plane of the ring. [35] The antibonding orbital (π *) and nonbonding orbital (n) are derived from sp 2 carbon and the lone pair electrons of N atoms, respectively. [36] The dark transition, S 0 →S 1 , belongs to n→π * transition under light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the N atom in p‐CN has the structure of an imine with enhanced stability due to aromaticity. The axis of the N lone pair electrons lies in the plane of the ring . The antibonding orbital (π*) and nonbonding orbital ( n ) are derived from sp 2 carbon and the lone pair electrons of N atoms, respectively .…”
Section: Resultsmentioning
confidence: 99%